An atom efficient, single-source precursor route to plasmonic CuS nanocrystals. Issue 2 (14th November 2018) - Mann, Patrick Bergstrom; McGregor, Iain J.; Bourke, Struan; Burkitt-Gray, Mary; Fairclough, Simon; Ma, Michelle T.; Hogarth, Graeme; Thanou, Maya; Long, Nicholas; Green, Mark
Abstract : The synthesis of colloidal semiconductor nanocrystals (NCs) from single-source precursors offers simplified manufacturing processes at the cost of reduced atom efficiency. Abstract : The synthesis of colloidal semiconductor nanocrystals (NCs) from single-source precursors offers simplified manufacturing processes at the cost of reduced atom efficiency. Self-capping routes have the potential to maximise this efficiency although investigation has so far been limited to organic solvents. Here we present the synthesis of copper sulfide NCs via the decomposition of a copper dithiocarbamate complex in water. Nanocrystalline covellite particles were prepared without the need for additional capping ligand and exhibited a hollow nanosphere morphology. Mass spectrometry of the water-stable NCs indicated the presence of a number of surface ligands, including a small amine fragment of the single-source precursor (SSP) complex. A broad plasmon resonance in the near-infrared (NIR) at 990 nm was also observed and the photothermal effect of this demonstrated. Cytotoxicity experiments indicated cell viability remained above 95% for NC concentrations up to 1 mg mL −1, indicating high biocompatibility.